Organisational determinants of evaluation maturity in the public sector: A resource-based perspective - Anis Ben Brik (19239442) (2025)
This study examines the organisational determinants influencing evaluation maturity in the Jordanian public sector, focusing on the interplay of leadership, organisational culture, structure and resource allocation. Grounded in the Resource-Based View theory, the findings indicate that organisational culture is the most significant determinant of evaluation maturity, while resource allocation also plays a crucial role. Although leadership initially demonstrates promise in influencing evaluation practices, its significance diminishes when contextual factors are considered. This suggests that effective evaluation practices are contingent on a supportive organisational culture and adequate resources. The implications of this study extend to public administration reform, emphasising the need for holistic approaches that integrate cultural and resource considerations to enhance evaluation maturity. Other Information Published in: Evaluation License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/13563890251347270